2013
DOI: 10.1111/dme.12197
|View full text |Cite
|
Sign up to set email alerts
|

Progression of chronic kidney disease in a multi‐ethnic community cohort of patients with diabetes mellitus

Abstract: Objective The present study investigates the impact of quality of care (QoC) and other factors on chronic kidney disease (CKD) stage progression among Type 2 Diabetes Mellitus (T2DM) patients. Methods This study employed a retrospective cohort from a nationwide Diabetes and Hypertension study involving 595 Thai hospitals. T2DM patients who were observed at least 2 times in the 3 years follow-up (between 2011-2013) were included in our study. Ordinal logistic mixed effect regression modeling was used to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 21 publications
3
37
2
1
Order By: Relevance
“…Our findings did not confirm the observations made by previous studies that there is more rapid progression of CKD in South Asian patients (Burden et al, 1992;Dreyer et al, 2013;Roderick et al, 1996). While these studies revealed significantly increased acceptance rates for renal replacement treatment in Asian and black populations, possible data inaccuracies, true increase in incidence and prevalence of underlying diseases, different genetic and environmental susceptibility to progression of CKD, referral for treatment, and access factors may have contributed to this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings did not confirm the observations made by previous studies that there is more rapid progression of CKD in South Asian patients (Burden et al, 1992;Dreyer et al, 2013;Roderick et al, 1996). While these studies revealed significantly increased acceptance rates for renal replacement treatment in Asian and black populations, possible data inaccuracies, true increase in incidence and prevalence of underlying diseases, different genetic and environmental susceptibility to progression of CKD, referral for treatment, and access factors may have contributed to this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Very little data are available regarding ethnic differences in DN in more contemporary populations, benefitting from more modern approaches to diabetes management. Recently, Dreyer, Hull, Mathur, Chesser, and Yaqoob (2013) examined differences in renal decline between South Asian and White European patients with DM in the primary care setting. They observed a 0.31 ml/min/1.73 m 2 greater decline in estimated glomerular filtration rate (eGFR) in the South Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…7 In November 2012, demographic, clinical, and prescribing data were extracted for all patients aged ≥18 years, registered with 102 general practices across Tower Hamlets, Newham, and City & Hackney. All data were anonymous and managed according to UK NHS information governance requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is of great concern in South Asians (SAs), a population with a high prevalence of diabetes, hypertension and kidney disease progression [1,2]. Obesity is a risk factor for CKD, but less is known about the role of regional body composition [3].…”
mentioning
confidence: 99%